Biodiveristy of Benthic Macroinvertebrates Family and its Relationship with Environmental Condition in High Altitude Lake: A Case Study of Situ Patengan: Biodiversitas Famili Makroavertebrata Bentik dan Hubungannya dengan Kondisi Lingkungan di Perairan Danau Dataran Tinggi: Studi Kasus Situ Patengan - Nurcahyanto, Arif; Krisanti, Majariana; Kurnia, Rahmat (Habitus Aquatica, 2023)
Situ Patengan is one of the highland lakes in West Java which is at an altitude of 1600 meters above sea level. Upland lakes have unique characteristics and are inhabited by various organisms including benthic macroinvertebrates. The purpose of this study was to examine the biodiversity of benthic macroinvertebrates at the family level and their relationship with aquatic environmental conditions. This study was carried out from August to October 2022 in three areas with 9 observation points. The results of this study obtained 9 families (Atyiidae, Glossiphonidae, Isotomidae, Chironomidae, Culicidae, Perlidae, Naididae, Lumbriculidae and Tubificidae) from 6 orders. The Chironomidae family is the dominating family in terms of number of species and abundance. Based on the Canonical Correspondence Analysis (CCA), each observation area has different water characteristics and correlations with benthic macroinvertebrates according to the environmental pressures that exist around the area. Even though some areas have quite high environmental pressure, there are still species of macroinvertebrates that are sensitive to environmental pressure, such as the Atyiidae and Perlidae families, especially in areas with relatively low environmental pressure, especially around protected forest areas.